Promoting Wayang Kulit as a Media in Internalizing Islamic Values - Ferdi Arifin (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2018)
Despite a wide array of research on wayang kulit (shadow puppets), scant attention has exposed the correlation between wayang kulit performances and learning media. As a local wisdom, wayang kulit promotes many benefits, especially in solving some educational issues in Indonesia, including students’ low motivation as well as their moral decadency. This present study aims to explore the use of wayang kulit as a media in internalizing Islamic values, especially the language used in its performance. A qualitative descriptive approach was employed in this research by using cognitive linguistic theory. The findings demonstrate that wayang kulit as intangible culture heritage of humanity leads today’s society to learn social life in the past to be applied in current condition, including the learning process of Islamic education. Another result reveals that language usage of wayang kulit provides us with the characters of Indonesian ancestors’ minds, motivation, honesty, loyalty, and good integrity. It indicates that this study offers that wayang kulit can play a role as one of learning media in fostering Islamic values